2014
DOI: 10.4236/msce.2014.21010
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of CeB6 Nanotubes

Abstract: This work presents the results of joint electroreduction of tetrafluorborate and cerium-ions, and determines the conditions of electrochemical synthesis of cerium borides in KCl-NaCl melts at the 973 K on tungsten electrode by the linear and cyclic voltammetry. Based on the current-voltage studies the optimal modes of cerium boride electrodeposition were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
(4 reference statements)
1
5
0
Order By: Relevance
“…By comparing these Figures (Figures 3-A and B), it can be concluded that semi-spherical MgO NPs were removed via leaching. On the other hand, in accordance to XRD result ( Figure 2) and TEM image (Figure 3-B), the phase component of the semi-cubic particles is CeB 6 . It can be seen that these NPs have curved corners.…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…By comparing these Figures (Figures 3-A and B), it can be concluded that semi-spherical MgO NPs were removed via leaching. On the other hand, in accordance to XRD result ( Figure 2) and TEM image (Figure 3-B), the phase component of the semi-cubic particles is CeB 6 . It can be seen that these NPs have curved corners.…”
Section: Introductionsupporting
confidence: 74%
“…In addition, the allocated score of profile fitting via the search/match software (PANalytical X'Pert HighScore) was 95%. Therefore, according to (i) tiny difference between the standard and calculated lattice parameter values, (ii) the high degree of crystallinity and (iii) high score of profile fitting, it can be concluded that this method can be a very effective technique to synthesize high-crystalline and high-quality CeB 6 NPs. Figure 3 shows TEM micrographs of the as-synthesized NPs before and after leaching process.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations